O papel do tutor na formação a distância do professor da Educação Básica - Almeida, Patrícia de Melo Pinto de (2016)
This research has as study objective the non-licensed tutor role who acts in the training of teachers from initial grades of basic education in Pedagogy majors provided at distance. The technology which involves the knowledge and keeps the relationship between the learning subject and the component to be learnt, evokes facts from social and cultural scope, mainly ones experimented in work and citizenship practice, which, without question, influence in the training of the future professor who opts by graduation using Correspondence Course. In this context, the driving questions are around the specific training of the non-pedagogue tutor, related to the training of basic education professor, and also of your role in the distance modality. New possibilities arising from the discovery and generation of new knowledge puts the tutor as responsible for the articulation of knowledge of the correspondence course graduation, and also the construction of discussion spaces and autonomy of its students. Considering the possibilities, the tutor is the mediator of pedagogic training of his students and cooperates with the assistance and knowledge construction on behalf of the ones who choose teaching profession. These knowledge s presuppose freedom dialogue and action exercises, because they share daily life interpretations from its students during initial graduation on basic school. The methodological path starts from bibliographic research, documental analysis and content, supporting an Instrumental Case Study. The tutor, in its pedagogic journey, must appropriate himself of the epistemological, philosophical, theoretical and methodological aspects of information technology, and establish relationships between digital knowledge and pedagogical formation by which students look for. Still, appropriate and invest on tools doesn t necessarily mean improving the tutor s quality. The tutor, to apply his function, beyond the specific knowledge of Communication and Information Technology (CIT), needs pedagogical knowledge. To underlie his role on the formation of a new teacher, it becomes necessary to identify in the Pedagogy major resume the components which interfere in this training and articulate the use of the CIT s in which are grounded. In this sense, this research brings an indication of insertion in public politics regarding the tutor as an education professional